Optimizing the synthesis of alumina inserts using hot isostatic pressing (HIP) - Ariff, Tasnim Firdaus; Azhar, Ahmad Zahirani; Sariff, Mohamad Nuresyam; Rasid, Syufiqa Nurfatin; Zahari, Siti Zulaikha; Bahar, Rubina; Karim, A.N. Mustafizul; Amin, A. K. M. Nurul (IOP Publishing, 2017)
Alumina or Aluminium Oxide (Al2O3) is well known for its high strength and hardness. Its low heat retention and low specific heat characteristics make it attractive to be used widely as a cutting tool for grinding, milling and turning processes. Various synthesis methods have been used for the purpose of enhancing the properties of the alumina inserts. However, the optimization process using Hot Isostatic Pressing (HIP) has not been performed. This research aims in finding the optimum parameters in synthesizing the alumina inserts (98Al2O3 1.6ZrO2 0.4MgO, 93Al2O3 6.4ZrO2 0.6MgO and 85Al2O3 14.5ZrO2 0.5MgO) using HIP at different temperatures (1200, 1250 and 1300°C) and sintering time (10, 30 and 60 minutes). Hardness, density, shrinkage and microstructure using SEM were analysed. The optimum sintering condition for the alumina insert was found in 98Al2O3 1.6ZrO2 0.4MgO sintered at 1300°C for 60 minutes for it exhibited the highest values of hardness (1917HV), density (3.95g/cm3), shrinkage (9.6%).